[BOOK REVIEW] China Grand Strategy: Contradictory Foreign Policy? - Rangga Amalul Akhli (The Republic of Indonesia Defense University, 2019)
Lukas K. Danner, China Grand Strategy: Contradictory Foreign Policy? Florida, USA: Palgrave Macmillan, 2018, 207 pp.ISBN 978-3-319-65777-6